Difference analysis of flavor characteristics of Jiangxiangxing Baijiu in Guizhou regions with different altitude - ZOU Feiyun, CHEN Mengqiang, LIU Fan, LI Tao, QIU Shuyi, ZHOU Hongxiang (Zhongguo niangzao, 2025)
To investigate the differences in volatile flavor components of sauce-flavor (Jiangxiangxing) Baijiu in Guizhou regions with different altitude, the volatile flavor components were determined by gas chromatography (GC) and electronic nose technique. The results were systematically evaluated using principal component analysis (PCA), orthogonal partial least squares-discriminant analysis (OPLS-DA), and cluster analysis (CA). The results showed that a total of 55 volatile flavor components in sauce-flavor Baijiu with different altitude regions were identified, and there were significant differences in their types and contents (P<0.05). Thirty-nine key aroma components (OAV>1) of sauce-flavor Baijiu in Guizhou regions with different altitude were screened based on odor activity values (OAV). High-altitude samples exhibited elevated levels of ester compounds such as ethyl pentanoate and ethyl nonanoate, along with alcohols including 1-propanol and 2-methyl-1-butanol, demonstrating complex aromatic profiles. Low-altitude samples were characterized by higher concentrations of ester aroma compounds (ethyl palmitate, ethyl linoleate, ethyl tetradecanoate, and ethyl octanoate) and pyrolytic compounds such as tetramethylpyrazine, contributing to intense flavor characteristics. Mid-altitude samples displayed relatively lower volatile flavor content with less pronounced aromatic complexity. Sauce-flavor Baijiu in Guizhou regions with different altitude were effectively distinguished by PCA and OPLS-DA. Using P-value of variance analysis and variable importance in the projection (VIP) values, a total of 27 key differential components (VIP>1, P<0.05) were screened. CA results indicated that there were significant differences in the content distribution of key differential substances of sauce-flavor Baijiu with different altitude regions.